Attitudes Toward Post-Traumatic Stress Disorder (PTSD) from an Islamic Perspective - Rustianti, Nora; Silvianetri, Silvianetri (The Future of Education Journal, 2025)
Post-Traumatic Stress Disorder (PTSD) is a psychological condition that can affect anyone who has experienced a traumatic event, such as a natural disaster, violence, an accident, or war. A spiritual approach plays a significant role in the healing process by providing moral and psychological guidance in facing life’s trials. This article aims to examine the appropriate attitudes that Muslims should adopt in dealing with PTSD, using a descriptive qualitative approach based on a literature review. Improving one's relationship with Allah, engaging in self-introspection, and practicing positive thinking are strategies offered by Islam to cope with PTSD.